HUMANITIES IN INDONESIA FOR A GLOBAL AGE - Anthony Reid (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
The 70th Anniversary provides an opportunity for reflection on the development of the Humanities in Indonesia, the achievements and the disappointments of a remarkable period. Indonesian Humanities scholars, and specifically those at UGM, have much to be proud of. They have built professional critical methods in a completely new language and context, without losing the critical approach to evidence. There have however been some disappointments and losses. Bahasa Indonesia’s gain has been many other languages’ loss. There is a danger that Humanities, in Indonesia as everywhere, may allow themselves to be restricted to a kind of heritage industry, preserving and coding the culture of ‘us’, as opposed to the complex interactions of the planet and beyond. The best way to counter the long-term decline of Humanities in the university may be the opposite, to embrace cultural diversity and interdependence.